EFEKTIVITAS MODELPEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA MATERI GEOMETRI DERAJAT DAN RADIAN DI KELAS X SMA NEGERI 2 DOLOK SANGGUL TP. 2019/2020 - Enita Octalia Siregar (LPPM Universitas HKBP Nommensen, 2024)
This study is an experimental research with a cooperative model. The population in this study were all tenth grade students at SMA Negeri 1 Tigalingga in the 2019/2020 academic year, consisting of 5 classes, namely class X MIA1, class XMIA2, class XMIA3, class XMIA4, class X MIA5. This study aims to determine how learning with the cooperative think pair share model and scientific approach should be towards students' abilities in understanding concepts and solving problems in exponent number operations in class X. The results of the study indicate that the design of the learning model that has been designed is good for use. Based on Table 4.8, the results of tcount = 10.002 and ttable = 1.67 (tcount> ttable) which means Ha2 is accepted. Thus, it can be concluded that learning with the cooperative Think Pair Share model is better than the scientific approach to understanding concepts in exponent number operations in class X of SMA Negeri 1 Tigalingga in the 2019/2020 academic year. Keywords: Creative Problem Solving, Concept Understanding